If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(1) + -3 = 0 Multiply -3 * 1 -3 + -3 = 0 Combine like terms: -3 + -3 = -6 -6 = 0 Solving -6 = 0 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| y=[100+.75(y-100)]+100+100 | | -8s+32=54 | | .66x+7=39 | | -9s+14=21 | | 2.4=0.3x+0.4y | | 2(3x+5)=5(x-4)-(5-3x) | | 12x+7c=315 | | (4x+2)(6-3x)= | | 400=x^2+42x | | 0=18x^2+90x-432 | | z6y4/z6y5 | | X^2-10x+20=8 | | a/6=7=11 | | -4s+30= | | -6z+12=24 | | -14-5n=2(5n+7)+5n | | (2x+3y)dx+(y+2)dy=0 | | -4s+15=25 | | (4x+2)+(5x-7)+3x=180 | | (2x-1)(5x^2+6x-3)= | | y^3+y=50 | | tanx=1.274 | | 187x=374 | | (2w^2-3w+1)(4w^2-7w-2)= | | 12=x+9-5x | | X+(-11)=13 | | x^2+y^2=1 | | (7x^2-5x-3)(2x+4)= | | X-(-9)=24 | | +2n=+4 | | 1/64 | | ln(3x-15)=5 |